2018
DOI: 10.5194/amt-11-3479-2018
|View full text |Cite
|
Sign up to set email alerts
|

Kinetically controlled glass transition measurement of organic aerosol thin films using broadband dielectric spectroscopy

Abstract: Abstract. Glass transitions from liquid to semi-solid and solid phase states have important implications for reactivity, growth, and cloud-forming (cloud condensation nuclei and ice nucleation) capabilities of secondary organic aerosols (SOAs). The small size and relatively low mass concentration of SOAs in the atmosphere make it difficult to measure atmospheric SOA glass transitions using conventional methods. To circumvent these difficulties, we have adapted a new technique for measuring glass-forming proper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 59 publications
6
36
0
Order By: Relevance
“…7) of toluene-derived SOA when compared with the other two types of SOA may enhance the hygroscopicity of the particle (Lambe et al, 2011b;Liu et al, 2018;Zhao et al, 2016) and thus may reduce the deposition IN ability of BC particles. On the other hand, Hinks et al (2018) shows that toluene-derived SOA also contains a significant amount of oligomers under dry laboratory conditions, similar to what we conducted in the PAM chamber in this study, potentially reducing the hygroscopicity and altering the phase state of the SOA to be semi-solid or solid (Li et al, 2020;Zhang et al, 2018b), under which the SOA can still nucleate ice (Zhang et al, 2019c). Overall, these two competing factors make our toluene SOA coating IN onset move towards but not fully in the homogeneous freezing regime, agreeing with the results of Kulkarni et al (2016).…”
Section: Ice Nucleation On Bc Coated With Soa Materialssupporting
confidence: 75%
“…7) of toluene-derived SOA when compared with the other two types of SOA may enhance the hygroscopicity of the particle (Lambe et al, 2011b;Liu et al, 2018;Zhao et al, 2016) and thus may reduce the deposition IN ability of BC particles. On the other hand, Hinks et al (2018) shows that toluene-derived SOA also contains a significant amount of oligomers under dry laboratory conditions, similar to what we conducted in the PAM chamber in this study, potentially reducing the hygroscopicity and altering the phase state of the SOA to be semi-solid or solid (Li et al, 2020;Zhang et al, 2018b), under which the SOA can still nucleate ice (Zhang et al, 2019c). Overall, these two competing factors make our toluene SOA coating IN onset move towards but not fully in the homogeneous freezing regime, agreeing with the results of Kulkarni et al (2016).…”
Section: Ice Nucleation On Bc Coated With Soa Materialssupporting
confidence: 75%
“…Three BC proxies were chosen to represent freshly emitted (in other words, unoxidized and more fractal) BC (R2500U), unoxidized compacted BC (R330R), and atmospheric chemically aged BC (COJ300). The morphological characteristics are within the value range of typical amounts of BC emitted from combustion sources and those collected in field observations (e.g., Lapuerta et al, 2007;China et al, 2013China et al, , 2014Vander Wal et al, 2014;China et al, 2015b;Y. Zhang et al, 2019a).…”
Section: Atmospheric Implicationssupporting
confidence: 60%
“…Champion et al (2019) found that SOA with higher condensed-phase fractions of extremely low volatility organic compounds (ELVOC) and low volatility organic compounds (LVOC) showed an increased viscosity. Zhang et al (2019) measured T g of isoprene SOA components including isoprene hydroxy hydroperoxide (ISOPOOH), isoprene-derived epoxydiol (IEPOX), 2-methyltetrols, and 2methyltetrol sulfates (2-MT-OS), observing a tight correlation between T g and vapor pressure.…”
Section: Introductionmentioning
confidence: 99%